Structured Literacy: A Framework for Teaching LESLLA - Christenson, Jennifer (LESLLA Symposium Proceedings, 2023)
Structured Literacy is an umbrella term for methods of teaching reading that are based on sound reading science. Teaching with a Structured Literacy approach in the earliest stages of reading development is characterized by a focus on building strong oral language skills as well as the explicit, systematic teaching of decoding skills. In middle and later stages, an emphasis on building fluency and increasing attention to comprehension is added. Structured Literacy is also characterized by elements that are intentionally excluded, particularly the use of the three-cueing method in early reading development, which involves teaching students to use guessing strategies as a primary means to figure out unknown words. This paper offers a Bridge Model to help teachers easily remember the elements of the Structured Literacy approach. The purpose of this paper is to share a framework for teaching LESLLA using a Structured Literacy approach, and explain how it can help teachers plan instruction for LESLLA students at various stages of literacy development.